2016
DOI: 10.1155/2016/7047910
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Views on a Combined Action Observation and Motor Imagery Intervention for Parkinson’s Disease

Abstract: Background. Action observation and motor imagery activate neural structures involved in action execution, thereby facilitating movement and learning. Although some benefits of action observation and motor imagery have been reported in Parkinson's disease (PD), methods have been based on stroke rehabilitation and may be less suitable for PD. Moreover, previous studies have focused on either observation or imagery, yet combining these enhances effects in healthy participants. The present study explores the feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 55 publications
(60 reference statements)
2
19
0
Order By: Relevance
“…In particular , it has been proposed that impaired social‐perceptive processing in PD may be related to dysfunction of the mirror neuron system (Alegre et al ., ); however, our results suggest that activation of this system in people with mild‐to‐moderate PD is similar to that of healthy older adults. Additionally, people with PD report engaging in behavioural mimicry in social situations (e.g., mirroring a partner's hand gestures; Bek et al ., ), and show appropriate spontaneous facial expressions in response to emotional and social context (Simons, Pasqualini, Reddy, & Wood, ). Nevertheless, because of a general reduction in spontaneous actions, overt signs of motor resonance may be less apparent in PD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular , it has been proposed that impaired social‐perceptive processing in PD may be related to dysfunction of the mirror neuron system (Alegre et al ., ); however, our results suggest that activation of this system in people with mild‐to‐moderate PD is similar to that of healthy older adults. Additionally, people with PD report engaging in behavioural mimicry in social situations (e.g., mirroring a partner's hand gestures; Bek et al ., ), and show appropriate spontaneous facial expressions in response to emotional and social context (Simons, Pasqualini, Reddy, & Wood, ). Nevertheless, because of a general reduction in spontaneous actions, overt signs of motor resonance may be less apparent in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneous nature of PD, "personalised treatments" has been identified as a research priority by people with PD [8] to address the broad range of everyday activities that individuals may find difficult (e.g., [7]). In this respect, training based on action representation (AO and MI) can be tailored to the individual's needs and rehabilitation goals.…”
Section: A User-informed Personalised Home-based Ao+mi Intervention mentioning
confidence: 99%
“…The feasibility of other home interventions using digital technology in PD has been reported, such as "exergame" activities focused on movement timing and coordination (e.g., [55,56]), and if effective, this approach could provide a widely accessible, low-cost alternative or supplement to existing rehabilitation programmes. A previous focus group with people with PD [7] explored views on the proposed ACTION-PD intervention, as well as individuals' understanding and experiences of AO and MI. The focus group indicated that a home-based combined AO+MI intervention would be acceptable and useful for people with mild to moderate PD.…”
Section: A User-informed Personalised Home-based Ao+mi Intervention mentioning
confidence: 99%
See 2 more Smart Citations